Acute ethanol treatment upregulates th1, th2, and hdc in larval zebrafish in stable networks - Puttonen, Henri; Sundvik, Maria; Rozov, Stanislav; Chen, Yu-Chia; Panula, Pertti (Frontiers in Neural Circuits, 2013)
Earlier studies in zebrafish have revealed that acutely given ethanol has a stimulatory effect on locomotion in fish larvae but the mechanism of this effect has not been revealed. We studied the effects of ethanol concentrations between 0.75% and 3.00% on 7-day-old larval zebrafish (Danio rerio) of the Turku strain. At 0.75-3% concentrations ethanol increased swimming speed during the first minute. At 3% the swimming speed decreased rapidly after the first minute, whereas at 0.75 and 1.5% a prolonged increase in swimming speed was seen. At the highest ethanol concentration dopamine levels decreased significantly after a 10-min treatment. We found that ethanol upregulates key genes involved in the biosynthesis of histamine (hdc) and dopamine (th1 and th2) following a short 10-min ethanol treatment, measured by qPCR. Using in situ hybridisation and immunohistochemistry, we further discovered that the morphology of the histaminergic and dopaminergic neurons and networks in the larval zebrafish brain was unaffected by both the 10-min and a longer 30-min treatment. The results suggest that acute ethanol rapidly decreases dopamine levels, and activates both forms or th to replenish the dopamine stores within 30 minutes. The dynamic changes in histaminergic and dopaminergic system enzymes occured in the same cells which normally express the transcripts. As both dopamine and histamine are known to be involved in the behavioural effects of ethanol and locomotor stimulation, these results suggest that rapid adaptations of these networks are associated with altered locomotor activity.